Key Concepts for Critical Infrastructure Research (Springer Fachmedien Wiesbaden : VS, 2018)
The discussion of critical infrastructures is dominated by the use of the interlinked concepts "criticality", "vulnerability", "resilience", and "preparedness and prevention". These terms can be detected in public discourse as well as in scientific debates. Often, they are used simultaneously in a normative as well as in a descriptive way. The PhD candidates of the interdisciplinary Research Training Group KRITIS at Technische Universität Darmstadt examine these concepts systematically one by one and discuss the links between them. They give a critical overview over the uses and limitations of these concepts. Informed by the approaches in Science and Technology Studies, they focus on the interrelatedness of technology and society. The book aims at creating a common ground for interdisciplinary infrastructure research. The authors are from history, philosophy, political science, civil engineering, urban and spatial planning and computer science. Contents Criticality Vulnerability Resilience Preparedness and Prevention Relations between the Concepts Target Groups Researchers and students in the fields of history, philosophy, political sciences, sociology, civil engineering, security research, planning Infrastructure planners, urban planners, politicians The Editor Dr. Jens Ivo Engels is a professor of Modern and Contemporary History at Technische Universität Darmstadt, Germany, and a spokesperson of the Research Training Group KRITIS.